Applicability of gas chromatography/quadrupole‐Orbitrap mass spectrometry in support of pharmaceutical research and development†. (29th February 2016) - Baldwin, Stephen; Bristow, Tony; Ray, Andrew; Rome, Karen; Sanderson, Natalie; Sims, Martin; Cojocariu, Cristian; Silcock, Paul
Abstract : Rationale: Gas chromatography/mass spectrometry (GC/MS) is a fundamental tool used to identify impurities throughout the active pharmaceutical ingredients development process. The coupling of Orbitrap mass spectrometry with GC marks an exciting advance in capability for GC/MS, offering a significant step change in resolving power, mass accuracy, sensitivity and linear range. Methods: A range of pharmaceutically relevant samples representing typical starting materials has been investigated with particular reference to impurity identification. The mass accuracy in Electron Ionisation (EI) and Chemical Ionisation (CI) was investigated for impurity identification. The linearity and mass accuracy over a wide dynamic range were evaluated. The number of scans obtained across chromatographic peaks was assessed at various resolution settings from 15, 000 to 120, 000 (full width at half maximum (FWHM) at m / z 200). Results: All the accurate mass measurements for impurities were within <1 ppm of the theoretical m / z value. The scan speed at the highest resolution produced 11 scans across the peak, and the mass accuracy for all scans was consistently <1 ppm – sufficient for impurity investigations and quantitative analysis. Linearity was demonstrated for N, N, N '‐trimethylethylenediamine over a concentration range of 0.0001 to 0.1250 μg/mL (w/v) with a correlation coefficient R 2 = 0.9996 and mass accuracy across all concentrations at <1.1 ppm. Conclusions: GC/Orbitrap MS has been evaluated for both qualitative and quantitative analysis of typical pharmaceutical precursors and impurities. Accurate mass measurement across a wide dynamic range, linearity and the ability to identify impurities in EI and CI illustrate that this instrument is a powerful tool of great benefit to pharmaceutical analysis.